Has the Integrated Medical Insurance System promoted return-to-hometown entrepreneurship among migrant workers? Evidence from China - Huang, Pengcheng; Sun, Zhengxiu; Li, Linfang; Li, Jia (Frontiers in Public Health, 2024)
An important way to reduce urban-rural disparity lies in encouraging migrant workers to return to their hometowns for entrepreneurship. This paper examines the effect of the Integrated Medical Insurance System on the return-to-hometown entrepreneurship among migrant workers. Using microdata from the China Household Finance Survey (CHFS) spanning from 2013 to 2019, we find that the Integrated Medical Insurance System (IMIS) significantly increases the likelihood of migrant workers returning to their hometowns for entrepreneurship by 0.44%. This result remains stable after a series of robustness checks. Heterogeneity results indicate that this "pullback effect" is more pronounced for those who are male and with lower educational levels, higher income, larger social networks, and lower risk preferences. Finally, the interaction between the Mass Entrepreneurship and Innovation policy (MEI) and IMIS can create a more significant combined effect in promoting the return of migrant workers to their hometowns for entrepreneurial activities.